Development and validation of doctor-patient relationship scale in China - Zeng, W. L. (2018)
Objective: To develop a scale of the doctor-patient relationship in China (DPR-C). Methods: A scale was developed by literature reviews and expert interviews and tested among 162 doctors,then was validated and empirically examined with 1971 doctors nationwide using exploratory factor analysis (EFA),confirmatory factor analysis (CFA) and other statistical methods,verified the reliability and validity of the scale. Results: The DPR-C has10 items,which includes two factors,“trust between doctor and patient” and “patient-centered treatment”. Conclusion:The scale has satisfactory reliability and validity, which can be used to measure the doctor-patient relationship from doctor’s perspective in China.